2021
DOI: 10.2174/1573399816666200703190437
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis on Efficacy of Exercise on Posture and Balance in Patients Suffering from Diabetic Neuropathy

Abstract: Background: Peripheral neuropathy is a major and chronic complication of diabetes mellitus affecting more than 50% of patients suffering from diabetes. There is involvement of both large and small diameter nerve fibres leading to altered somatosensory and motor sensations, thereby causing impaired balance and postural instability. Objective: To assess the effects of exercises on posture and balance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…Upon reviewing the literature, there is support that exercise-based interventions ≥4 weeks are beneficial for patients with DPN. This conclusion falls in line with other recently conducted literature reviews investigating the effects of exercise on enhancing gait function [ 156 ], decreasing neuropathic pain [ 157 ], and improving posture and balance among patients with peripheral neuropathy [ 158 ]. However, though the results of this review find various modalities of exercise to be beneficial, the effects are quite numerous and at times, inconsistent.…”
Section: Discussionsupporting
confidence: 91%
“…Upon reviewing the literature, there is support that exercise-based interventions ≥4 weeks are beneficial for patients with DPN. This conclusion falls in line with other recently conducted literature reviews investigating the effects of exercise on enhancing gait function [ 156 ], decreasing neuropathic pain [ 157 ], and improving posture and balance among patients with peripheral neuropathy [ 158 ]. However, though the results of this review find various modalities of exercise to be beneficial, the effects are quite numerous and at times, inconsistent.…”
Section: Discussionsupporting
confidence: 91%
“…This reminds the future analysis could conduct subgroup analysis based on different participants (T2DM with or without DPN) if there are enough studies. Consistent with a previous review, 47 various exercise interventions had a significant effect in improving BBS and posture stability in diabetes patients. A recent systematic review 25 showed that Tai Chi did not exert an impact on balance (single leg stance test), but it just pooled data from 2 studies.…”
Section: Discussionsupporting
confidence: 88%
“…In a systematic review by Tofthagen et al [ 36 ], the authors summarise the existing literature on the effectiveness of plyometric and balance training interventions in people at high risk of falls and conclude that plyometric and balance training is recommended to be safe and effective in older people at high risk of falls and in the DPN population. A systematic review and meta-analysis by Thukral et al [ 37 ], in which 18 randomized controlled trials were also pooled, showed that the use of different exercises (e.g. balance exercises, core stability exercises, Tai Chi, proprioceptive exercises, etc.)…”
Section: Discussionmentioning
confidence: 99%